A importância da contextualização histórica nas aulas das teorias einsteinianas aplicadas ao ensino médio - Rodrigues, Giulianno Raposo (2019)
This MSc dissertation of PPGECIM (Programa de Pós Graduação em Ciências e Matemática) comes to defend and research the importance of historical contextualization in physics classes applied to high school students. More specifically, lectures will be given on Einstein's theories, in particular the Restricted Relativity and the photoelectric effect in light of the Quantum theory with a vast historical background that involved the backstage of the life of the greatest physicist of mankind: Albert Einstein. It will be treated the multiplicities of his personality that go from his genius and pioneering, to social and political involvement with the academic environment, governmental entities and society in general, to aspects of their personal lives. Through this research we will try to understand the stimuli created in our students and the contribution to the apprehension of the theoretical contents, when submitted to resources that will bring the historical trajectory of the development of Einstein's theories and their unfolding. Finally, we will propose na educational product that uses information technology by creating a virtual platform on Google Drive where students can use to post short duration videos and also have full access to this dissertation.